Effect of increased reliance on specific excise on the consumption of cigarettes - Kilumelume, Micheal (School of Economics, 2019)
Research has shown that specific tax is more effective in discouraging the behavior of smoking than ad valorem tax. This paper makes use of panel data on 39 countries to investigate the impact of increased reliance on specific tax on cigarette consumption. The data used includes 21 countries, from six WHO regions, that increased their reliance on specific tax between 2008 and 2016. The fixed effects and random effects models are employed to estimate the extent to which a change in the specific share of excise tax changes the per capita consumption of cigarettes. According to the results, a one percent increase in the share of specific tax is associated with a 0.16 percent decline in per capita consumption. The findings support the assertion that increased reliance on specific tax results in a more significant decline cigarette consumption. The paper recommends that policymakers should aim to implement a health-driven taxation policy which entails a heavy reliance on specific tax on cigarettes and other tobacco products. However, it is essential to keep in mind that reliance on specific tax may only be useful when adopted with along with other strategies of tobacco control such as combating illicit trade.